Investigation of the Academic Motivations of the Students Studying Through Distance Education System in Terms of Some Variables / a Case Study of Sakarya University - Omeroglu, Engin; KELESOGLU, Fikri (International Journal of Scientific Research and Management (IJSRM), 2020)
Motivation is one of the important elements for the sustainability of a behaviour. One condition of learning is that it leaves a permanent mark. One of the main references that will ensure this permanence in distance education is the academic performance of individuals. In this research, the students' academic motivations regarding online courses (virtual classes), who study through distance education system in some departments of Sakarya University were examined according to some variables, and the reasons for the low attendance rates in online courses (virtual classes) were investigated.  The universe of the research consisted of students who studied at Sakarya University through distance education system while the study sample consisted of 660 students selected by random sampling method. Questionnaires and scales were delivered to the sample group via email. In the research, the "Academic Motivation Scale", adapted to Turkey by Karagüven (2012) and the questionnaire prepared by the researchers, asking about some demographic data were used, and the data obtained were analyzed with SPSS software.  In this context, the results obtained from the research are as follows: It was observed that there was a significant difference between the lower dimensions of academic motivation levels and the gender, age, marital and employment status variables of the students who continued their education through online courses by distance education method at Sakarya University. It was found that there were no significant differences between some sub-dimensions of academic motivation and variables. At the end of the study, recommendations for gender, age, marital status and employment status were developed.